Strategi Guru dalam Membina Akhlak Mulia pada Siswa di Sekolah: Teachers' Strategies in Cultivating Noble Morals in Students at School - Anggraeni, Nia; Sumarna, Elan; Budiyanti, Nurti (STAI Publisistik Thawalib Jakarta, 2024)
This research aims to map the strategies used by teachers in fostering noble morals in students at Negeri 74 Bandung Junior High School, especially to overcome the problem of juvenile delinquency which often occurs. This research approach is qualitative using the case study method. Data collection techniques used include observation, in-depth interviews, and documentation analysis. Primary data was obtained through interviews with teachers and related parties, while secondary data was collected from various relevant literature. To analyze the data, this research applies steps such as data reduction, data presentation, drawing conclusions, and verification which ensures the validity of the findings. The data validation technique used is triangulation. The results of this research show that the moral development strategies implemented in schools include: The five-minute movement program for reading the Al-Qur'an before studying, extracurricular reading and writing of the Al-Qur'an, the habit of doing dhuha prayers in congregation, express Islamic boarding schools, Islamic studies, connecting lesson material with good morals, as well as providing rewards and coaching. The strategies through these programs are quite effective in dealing with various forms of student delinquency. These findings highlight the importance of the proactive role of teachers and close collaboration between schools and parents in creating an educational environment that is conducive to the development of better student morals